The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.11648/j.ajns.20150404.11
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Learning Style and Undergraduate Nursing Students’ Academic Achievement in School of Nursing and Midwifery, Tehran University of Medical Sciences, Tehran, Iran

Abstract: Background: The Learning style has been the focus of numerous studies, but it remains complex and affected by many factors. Nursing students should learn large quantities of theoretical content in a short period of time. Objective: The Relationship between Learning style and undergraduate nursing students' Academic Achievement in School of nursing and midwifery, Tehran University of Medical Sciences, Tehran, Iran Methods: A correlational cross sectional study was conducted. The subjects of this study were Unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Piane et al 28 also found that students with the assimilative learning style had higher scores on theoretical tests than students with the other three styles. This disparity in the results of studies might be explained by heterogeneity in the study population; previous studies mostly included only one group of students, for example, medical or nursing, 11,12 and the instrument used to assess learning style. 24 The results of this study showed that female students had higher academic achievement compared to male students, which is consistent with the results of other studies 29,30 that showed academic performance of female students was higher than male students.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Piane et al 28 also found that students with the assimilative learning style had higher scores on theoretical tests than students with the other three styles. This disparity in the results of studies might be explained by heterogeneity in the study population; previous studies mostly included only one group of students, for example, medical or nursing, 11,12 and the instrument used to assess learning style. 24 The results of this study showed that female students had higher academic achievement compared to male students, which is consistent with the results of other studies 29,30 that showed academic performance of female students was higher than male students.…”
Section: Discussionmentioning
confidence: 99%
“…7 There are studies attempt to assess learning styles among university students [8][9][10] as well as the association between academic achievement and learning styles. [11][12][13] A review of the literature regarding students' learning style and academic achievement including students from all medical disciplines (from medicine to health sciences) is not sufficient. Previous studies often included only one group of students (for example, medical or nursing).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation